Peningkatan Produktivitas UMKM Mille Crepes “Kirimi Dessert” - Desak Made Sukarnasih; Dewa Ayu Kadek Pramita; Desak Ayu Sriary Bhegawati (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
The COVID-19 pandemic has had a significant impact on the Small and Medium Enterprises (SMEs) sector, including Kirimi dessert, a home store located on Jalan Noja I, Kesiman Petilan Village, Denpasar. This study aims to identify problems and provide solutions for Kirimi dessert MSMEs in facing challenges during the pandemic. The business, which focuses on making mille crepes and various desserts, faces several main obstacles such as limited production space, inability to fulfil orders when demand is high, and lack of promotion and personal branding. The research methodology used a qualitative approach through interviews and discussions with the business owner. The solutions offered include the development of MSME innovation, business expansion, and increased promotion through logo design, packaging, and social media optimisation. The implementation of this solution is expected to help MSMEs increase market reach and sales during the COVID-19 pandemic.